Price and Monetary Dynamics Under Alternative Exchange Rate Regimes - Bleaney, M. (IMF Working Papers; Working Paper, 1999)
According to theory, inflation persistence should have less variance across countries under pegged than floating exchange rates, but not necessarily a lower mean. The paper tests this prediction on postwar data for OECD countries. After allowing for the upward bias to persistence estimates created by shifts in mean inflation, the paper finds persistence has a greater spread (but not a higher mean) in the floating-rate period, as predicted by theory. Monetary growth has been much less accommodative of inflation under floating rates, most probably because of the shifts in monetary policy rather than those in exchange rate regime.